Length-weight relationship of Threadfin Bream (Nemipterus sp.) in Village Malang Rapat Waters, Bintan Regency, Riau Island - Rapita Rapita; Susiana Susiana; Rochmady Rochmady (Sangia Publishing, 2020)
Village Malang Rapat waters are have the potential and habitat of kurisi fish resources (Nemipterus sp.). The research was to determine the length-weight relationship of kurisi fish (Nemipterus sp.) in Village Malang Rapat. Sampling of kurisi fish (Nemipterus sp.) in two months (October-November 2020) is taken once a week based on fishing grounds and habitat. Length-weight relationship of female and male kurisi fish (Nemipterus sp.) were y = 1,1568x2,0659 and y = 1,2123x1,8971 respectively, based on this value show that female and male kurisi fish (Nemipterus sp.) in Village Malang Rapat waters have negative allometric growth patterns (b < 3).